Status and prospects of improvement of physical education of lawyers - Миргород Діана Олексіївна (Diana Myrgorod); Коломійцева Ольга Едуардівна (Olga Kolomiytseva) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to examine the condition and prospects of improving the system of physical education in higher legal education. Material and Methods: for research methods were used: analysis and synthesis of scientific and methodical literature, teacher observations, the method of expert evaluation. Results: it was shown that for every legal specialization, there is only one optimal system factor, which provides maximum and reliable implementation of the tasks of professional activity in a certain period of time. Thus, a factor which the functional system of professional activities of lawyers to law enforcement officials of MIA of Ukraine performs the final result, which is different for specific professional activities. Conclusions: improving the process of preparing future lawyers law enforcement activities should be completed as in the direction of developing a comprehensive system of physical education with a graded approach to the specifics of the legal profession and the use of modern means of training. This technology education, in our opinion, will significantly reduce the time of social, psychological and physical adaptation to the characteristics of the students training in high school and the specific professional activity.